PEMBENTUKAN KARAKTER TANGGUNG JAWAB SISWA MELALUI PEMBELAJARAN PPKn SECARA HYBRID LEARNING DI SMP NEGERI 9 SURABAYA - Yulda Cahyaning Utami; Harmanto Harmanto (Kajian Moral dan Kewarganegaraan, 2022)
The purpose of this study was to describe the strategies, obstacles, and solutions of civics teachers in shaping the responsibility character of students through hybrid learning at SMP Negeri 9 Surabaya. This study uses a qualitative approch with a descriptive method. The informants in this study were three people, one teacher and two student of VII class. The data analysis of this research refers to the Miles and Huberman model which includes data collection, data reduction, and drawing conclusions based on Thomas Lickona’s character theory, namely moral knowledge (moral knowing), moral feeling (moral feeling), adn moral action (moral action) related to each other. The results showed that the character building of students’ responsibility in SMP Negeri 9 Surabaya was carried out by civic teachers through first, providing student learning motivation by providing understanding of student material, creating learning content and giving attention to students in receiving and doing assignments. Second, through examples of good habits including the teacher as a role model and habituation both before and after learning. Third, helping students learn from mistakes through punishment and self evaluation. The obstacles experienced by civic teachers in implementing this strategy stem from students’ social and economic factors, the live event learning policy for a maximum of four hours, and school policies that require parents to drop off and pick up students during live event learning. The solutions provided to overcome these obstacles are by providing device loans to students, tolerating delays in participating in learning and collecting assignments, as well as utilizing time in learning Keywords: Responsibility character, learning, Hybrid learning.